Pemenuhan Kebutuhan Produksi Beras Nasional Dalam Meningkatkan Kesejahteraan Masyarakat Menurut Perspektif Ekonomi Islam - Ariyanti, Septi Dwi; Nabila, Uyun; Rahmawati, Lilik (Prodi Ekonomi Syariah Universitas Majalengka, 2024)
As a country with a tropical climate, Indonesia is a country that has abundant agricultural commodities so that the majority of its population makes a living as farmers or works in the agricultural sector. Currently, the agricultural sector is a sector that is of concern to the government because it is a sector that contributes to the country's foreign exchange and is a source of income to meet the needs of its people. One of the most important food commodities is rice because it is the main staple consumed by the Indonesian population. Based on data from the Central Statistics Agency (BPS), Indonesia's population increases every year, but rice production is unstable. This will threaten Indonesia's food security to meet needs. The aim of this research is to analyze the availability of domestic rice to meet the needs of improving the welfare of the Indonesian people. The method used in this research is descriptive with a quantitative approach and secondary data from BPS. The analytical results obtained are that even though domestic rice production is very fluctuating or tends to decrease while Indonesia's population growth continues to increase every year, it turns out there is still a surplus in meeting the needs of the people during 2019-2023. Because the national rice availability is still in surplus, it can be concluded that Indonesia is still fulfilling its darruriyah (needs) and achieving maslahah to date and the welfare of its people is still maintained.